Clinical Electrotherapy - Nelson, R. M. Roger M; Currier, D. P. Dean P (Appleton and Lange, 1991)
This leading text provides you with the relevant physiology, instrumentation, and the general principles of electrical stimulation, and examines specific clinical areas of electrotherapy. This new edition is a result of rigorous restructuring of chapters to eliminate repetition and assure consistency of terminology. Electrotherapy nomenclature has been updated to reflect the current standards in practice according to the APTA Section on Clinical Electrophysiology. Clinical aspects of electrotherapy, including how to perform motor/sensory neuronal conduction and electromyography, have been added. Two new chapters detail the latest technology on magnetic stimulation and TENS.